Potencialidades da Moringa oleifera Lam na produção de biodiesel e no tratamento de água produzida na extração de petróleo - Pereira, Daiane Farias (2011)
Esters from vegetable oils have been considered an alternative for diesel substitution in compression-ignition engines. In Brazil, several kinds of oil plants, that have potential to be used as raw-material for biodiesel production, are cultivated, such as soybean, castor, sunflower, corn, oil palm and moringa. Moringa oleifera Lam is a tropical plant that belongs to the Moringaceae family, native to India. The oil extracted from its seeds shows good resistance to oxidation and contains high content of unsaturated fatty acids, especially oleic acid (78%). An important point is that moringa seeds can be used for oil extraction whereas their by-products can be useful for wastewater treatment. Then, this work intends to study the potentiality of moringa in biodiesel production by transesterification, hydroesterification and transesterification in situ reactions and in the treatment of the water produced from oil extraction, using the by-products (pod, cake and shell) in oil/water separation by filtration and coagulation/flocculation. Physical-chemical analyses were carried out aiming to characterize the oil obtained from moringa seeds. Reactions for biodiesel production were performed by the above-mentioned processes. In transesterification and transesterification in situ reactions, the alcohol (methanol and ethanol) and the catalyst (sodium or potassium hydroxide) were permuted; the temperature was kept constant at 25°C for one hour. Hydroesterification was carried out in a batch reactor using, for hydrolysis, 20% of niobium oxide (catalyst), oil/water ratio of 20:1 at 300°C for one-hour reaction. Esterification was performed with 20% of niobium catalyst and alcohol/fatty acid ratio of 3:1 at 300°C for one hour. Coagulationflocculation tests, with produced water, were carried out varying the concentration of moringa extract in salt and water medium. The filtration experiments took place in a bench-scale PVC tube. The shell, the cake (obtained from transesterification in situ) and the pod of moringa were used as filter media, whose efficiency were compared to nut shell, which is commonly used by oil industries to remove oil and greases in water. The results showed an ester conversion higher than 90% in transesterification and hydroesterification reactions. Concerning the transesterification in situ, the oxidation stability stood out, being higher than 300 hours. In the studies of oil/water separation, the process of coagulation/flocculation was efficient, mainly when using the coagulant extracted on saline media. In this media, at a concentration of 0,5 mL/L, a oil removal of 96% was achieved. Regarding the filtration process, moringa shell was the most efficient media once an oil removal of 95% was achieved. The potentiality of moringa was observed in all the process of biodiesel production and water treatment studied in this work.